Development and characterization of a topical gel, containing lavender (Lavandula angustifolia) oil loaded solid lipid nanoparticles - Faeze Fahimnia; Mehran Nemattalab; Zahra Hesari (BMC, 2024)
Abstract Gels loaded with nanocarriers offer interesting ways to create novel therapeutic approaches by fusing the benefits of gel and nanotechnology. Clinical studies indicate that lavender oil (Lav-O) has a positive impact on accelerating wound healing properly based on its antimicrobial and anti-inflammatory effects. Initially Lav-O loaded Solid Lipid Nanoparticles (Lav-SLN) were prepared incorporating cholesterol and lecithin natural lipids and prepared SLNs were characterized. Next, a 3% SLN containing topical gel (Lav-SLN-G) was formulated using Carbopol 940. Both Lav-SLN and Lav-SLN-G were assessed in terms antibacterial effects against S. aureus. Lav-SLNs revealed a particle size of 19.24 nm, zeta potential of -21.6 mv and EE% of 75.46%. Formulated topical gel presented an acceptable pH and texture properties. Minimum Inhibitory/Bactericidal Concentration (MIC/MBC) against S. aureus for LAv-O, Lav-SLN and Lav-SLN-G were 0.12 and 0.24 mgml− 1, 0.05 and 0.19 mgml− 1 and 0.045, 0.09 mgml− 1, respectively. Therefore, SLN can be considered as an antimicrobial potentiating nano-carrier for delivery of Lav-O as an antimicrobial and anti-inflammatory agent in topical gel.